The Role Of Information Technology Utilization And Managerial Support In Optimizing Digital Bookkeeping For MSMEs - Narulita, Friska Dhea; Soraya, Bunga; Kustiwi, Irda Agustin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study examines the role of information technology and managerial support in optimizing digital bookkeeping of MSMEs in Indonesia. Using a descriptive qualitative approach through a literature review of 2020-2025 national journals, the research identified that digital bookkeeping applications, mobile applications, and cloud computing can improve the accuracy, efficiency, and transparency of MSME financial records. Despite the great potential, the implementation of these technologies is hampered by low digital literacy, limited infrastructure, and resistance to change. Managerial support in the form of leader commitment in providing training, building an adaptive culture, and allocating resources are key factors for successful digitization. The integration of information technology with accounting information systems creates financial management that is integrated with other aspects of the business, resulting in improved access to formal financial services and business growth. Improved digital training, adequate infrastructure, and cross-sector collaboration are recommended to create an inclusive digital ecosystem for MSMEs